Determinants of maternal near-miss in private hospitals in eastern Ethiopia: A nested case–control study - Shegaw Geze Tenaw (SAGE Publishing, 2021)
Objective: Maternal near-miss refers to a woman who nearly died but survived complications in pregnancy, childbirth, or within 42 days of termination of pregnancy. The study of maternal near-miss has become essential for improving the quality of obstetric care. The objective of this study was to identify the determinants of maternal near-miss among women admitted to major private hospitals in eastern Ethiopia. Method: An unmatched nested case–control study was conducted in major private hospitals in eastern Ethiopia from 5 March to 31 March 2020. Cases were women who fulfilled the sub-Saharan African maternal near-miss criteria and those admitted to the same hospitals but discharged without any complications under the sub-Saharan African maternal near-miss tool were controls. For each case, three corresponding women were randomly selected as controls. Factors associated with maternal near-misses were analyzed using binary and multiple logistic regressions with an adjusted odds ratio along with a 95% confidence interval. Finally, p-value < 0.05 was considered as a cut-off point for the significant association. Results: A total of 432 women (108 cases and 324 controls) participated in the study. History of prior cesarean section (AOR = 4.33; 95% CI = 2.36–7.94), anemia in index pregnancy (AOR = 4.38; 95% CI = 2.43–7.91), being ⩾ 35 years of age (AOR = 2.94; 95% CI = 1.37–6.24), not attending antenatal care (AOR = 3.11; 95% CI = 1.43–6.78), and history of chronic medical disorders (AOR = 2.18; 95% CI = 1.03–4.59) were independently associated with maternal near-miss. Conclusion: Maternal age ⩾ 35 years, had no antenatal care, had prior cesarean section, being anemic in index pregnancy, and have history of chronic medical disorders were the determinants of maternal near-miss. Improving maternal near-misses requires strengthening antenatal care (including supplementation of iron and folic acid to reduce anemia) and prioritizing women with a history of chronic medical illnesses. Interventions for preventing primary cesarean sections are crucial in this era of the cesarean epidemic to minimize its effect on maternal near-miss.